Evaluation of Internet Information about Lingual Orthodontics Using DISCERN and JAMA Tools - Hatice Kübra Olkun; Arzu Arı Demirkaya (Galenos Yayinevi, 2018)
Objective:To investigate the quality and reliability of websites providing information about lingual orthodontics in Turkish.Methods:An internet search was conducted on March 6th, 2017, using popular search engines in Turkey: GoogleTM, bingTM, YAHOO!®, and Yandex® for the keywords "lingual ortodonti, görünmeyen braketler, and görünmeyen teller". The top 10 websites for each keyword and search engine were examined, and duplicates, irrelevant websites, websites showing scientific articles, and orthodontic supplies market sites were excluded. The remaining 58 sites were assessed using the DISCERN instrument and JAMA benchmarksResults:The authors of the remaining sites were orthodontists (48%) and dentists (5%), while 46% of the websites did not state author names. Ninety-one percent lacked references, and 87% lacked a date. Only 30% were balanced and unbiased. The mean overall DISCERN score was very poor (43%) or poor (40%). Of the 58 websites, 48% (28 sites) met authorship, 7% (4 sites) attribution, 71% (41 sites) disclosed website ownership, and 3% (2) currency benchmarks of JAMA.Conclusion:Information on the internet related to lingual orthodontics is poor. Clinicians should warn patients that information on the internet about lingual orthodontics might be inadequate, and they should direct patients to higher-quality websites.